Analisis Risiko Keselamatan dan Kesehatan Kerja (K3) Dengan Metode Risk Assessment Matrix Risiko pada Proyek Pembangunan Apartemen Kyo Society di Surabaya: Studi Kasus Penilaian dan Manajemen Risiko pada Proyek Konstruksi Bangunan Tinggi (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Hasyim Asy'ari, 2024)
Occupational Health and Safety (OHS) is a critical element in construction projects, especially in high-risk Mechanical Electrical Plumbing (MEP) work. The Kyo Society Apartment Project in Surabaya, with PT. Alkonusa Teknik Interkon as a subcontractor for PT. Wika Gedung, faces challenges in ensuring optimal OHS implementation. This study uses the Risk Assessment Matrix method to identify and analyze risks. Data were collected through field observations and questionnaires, then analyzed to evaluate the risk levels and the success of OHS implementation. The study results show that medium-risk categories account for approximately 48% of the total tasks reviewed, indicating activities that significantly pose potential negative impacts on occupational safety and health. Specifically, in the context of HVAC work, activities falling under this category involve risks such as falling from heights, electric shocks, and exposure to high UV rays. These types of risks require strict supervision and adjustment of safety protocols for more effective risk mitigation and management. The low-risk category, comprising 52% of total activities, indicates the effectiveness of the risk control measures already implemented in certain operational segments. This suggests that existing safety practices are adequate to prevent serious incidents, supporting the fundamental principles of internal control and the application of safety protocols in construction projects.